Fidelity of implementation of activity-based intervention in daycare. Issue 9 (4th July 2022) - Lemire, Colombe; Dionne, Carmen; Rousseau, Michel
ABSTRACT: Despite the recognized effectiveness of naturalistic intervention practices, including activity-based intervention (ABI), challenges remain regarding their implementation. Assessing implementation fidelity can help understand factors that may influence their implementation. This study aims to document the evolution of ABI implementation fidelity (Adherence, Dosage, Quality and Participant responsiveness) in daycare settings following professional development. The participants are four educators. The current study uses an embedded design. The predominant aspect is quantitative, that is, single-case research design with three measurement phases of 12 observation moments. In terms of Dosage, an increase in the frequency of learning opportunities offered by educators is observed as the experiment progresses. For three educators, results show moderate and significant effects of professional development between Phases 1 and 3. A slight decrease in Quality can be observed when learning opportunities are adapted to children's developmental levels. This article highlights the importance of documenting several components of implementation fidelity.